Five ways to get a grip on teaching advocacy in medical education: the health humanities as a novel approach - Dhara, Arundhati; Fraser, Sarah (Canadian Medical Education Journal, 2024)
The advocate role is recognized as an intrinsic medical competency. Despite recent attention to pedagogical approaches, it is a role that remains poorly understood and difficult to teach. At the same time there is a growing body of evidence showing the necessity of incorporating humanities-based education into medical curricula. Here, we present five ways to use the humanities as a tool for teaching the advocate role including: decentring the physician as expert, fostering provider engagement, allowing for flexibility, making the humanities mandatory and normalizing narrative tools in education and practice.